A cascata de Xangô e os sujeitos de matriz africana: geografizando sentidos e espacialidades no município de Alvorada-RS - Lopes, Lazie Ronaldo Santos (2021)
The research presents a reflection on the spatialization processes from the construction of the African matrix subjects frequenting the Xangô Waterfall in the city of Alvorada, Rio Grande do Sul. The main objective is to investigate the existence of spatialities produced by subjects adept at African Cosmoperception from their relationship with the Cascade and its influence as a sacred space of resistance. From this premise we analyze African Cosmoperception as a builder of a universal Geography of things and senses. The methodology of the research is phenomenology from the conceptual arrangement of the Geography of Religion in the perspective of symbolic conformation. From the relationship of religious subjects with space, the concept of sacred space is built, thus generating expressions of social life, composing behaviors, experiences, temporalities and daily actions that compose possibilities of geographic analysis in the municipality of Alvorada. One of the founding concepts of the African Matrix culture is precisely orality, so the collection of narratives rather than a methodological procedure is embodied in an approach to the edifying principles of subject relationships and their perceptions and representations of the world. The experienced space known through the narratives brings us the spatial experience of these groups and their high symbolic consciousness. From the existential encounter at the Shanghai Waterfall and the accounts of these subjects we can build bridges between the perception of the African Matrix and Cassirer's phenomenology through his Symbolic Shapes Theory. It also enabled the knowledge of the influence of this perception in terms of spatiality production in the municipality of Alvorada. And, finally, the understanding of the central role of the subject in the relation\constitution of the geographic space from the mediation of Symbolic Forms.